2000
DOI: 10.4219/jeg-2000-574
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Motivation for Talent Development

Abstract: The main goal of this paper is to conceptualize a theory of optimal motivation for talent development. According to this theory, a lack of motivation can seriously undermine talent development. Optimal motivation is necessary for the full development of talent. Optimal motivation is described as a “flow” experience in which students become so absorbed in a task that they lose track of time and their efforts seem “effortless.” A generalized expectancy-value theory is used to analyze 3 ideal conditions under whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 42 publications
(47 reference statements)
0
34
0
4
Order By: Relevance
“…Prior studies have examined the effects of flow in higher education (Ghani, 1995;Kiili, 2005), foreign language studies (Egbert, 2003), music education (Custodero, 2002), education for the gifted (Rea, 2000), and instructional design using hypermedia (Chan & Ahern, 1999;Konradt, Filip, & Hoffman, 2003).…”
Section: Flow and Learning Outcomesmentioning
confidence: 98%
“…Prior studies have examined the effects of flow in higher education (Ghani, 1995;Kiili, 2005), foreign language studies (Egbert, 2003), music education (Custodero, 2002), education for the gifted (Rea, 2000), and instructional design using hypermedia (Chan & Ahern, 1999;Konradt, Filip, & Hoffman, 2003).…”
Section: Flow and Learning Outcomesmentioning
confidence: 98%
“…However, our study indicates that we have to broaden Rea's unit of analysis. Rea (2000) and Csikszentmihalyi et al (1993) were primarily concerned with the relationship between the educator and the learner, and the learner's egocentric experience of flow, whereas our approach encompasses the ecological niches around the students in order to understand how these flow zones come about. Therefore we suggest that successful ecological niches, and not only individual experiences, can be characterized as flow zones, i.e.…”
Section: How Does the Microclimate Support Doctoral Students?mentioning
confidence: 99%
“…In a study on optimal motivation for talent development, Rea (2000) suggested a prototypical model for the development of talent among students that balances serious-minded and fun-minded motivational processes. This balance creates a zone of optimal motivation -a so-called 'flow zone' -between the emotional extremes of anxiety and boredom.…”
Section: How Does the Microclimate Support Doctoral Students?mentioning
confidence: 99%
“…The assumption is that only in activities that are conducted with passion, peak performances (i.e., episodes of superior functioning; Privette, 1983) can be achieved (Seligman & Csikszentmihalyi, 2000). With the concept of 'passion', described as the inclination towards an activity one likes, finds important and in which one wants to invest energy (Vallerand et al, 2003), the essential role of motivation and interests in attaining excellence is highlighted (Rea, 2000). Giftedness and Talent (DMGT) and replaced the seven domains of human functioning he initially distinguished by six major occupational groups (i.e., technical, science and technology, arts, social service, administration and sales, and business operations) based on Holland's work on vocational interests.…”
Section: Operationalization Of Talent Into Two Componentsmentioning
confidence: 99%